CHLORPYRIFOS IMPAIRS HAEMATOLOGICAL AND HEPATIC TISSUE FUNCTIONS BY PRODUCING OXIDATIVE STRES - SUBAN BASKEY; MOURI GHOSH; PANCHALI TARAFDER; KAUSHIK SARKAR; GOUTAM PAUL (International Journal of Pharma and Bio Sciences, 2014)
Chlorpyrifos is a widely used organophosphate pesticide. The present study was undertaken to examine the effect of chlorpyrifos on haematological and blood biochemical variables in rat. Chlorpyrifos was administered orally to male rat in different doses (19.4, 38.8, 58.2mg/kg BW/day) for consecutive 10, 20, 30 days. We found that red blood cell (RBC) count and haemoglobin (Hb) level were decreased while total white blood cell (WBC) count was increased, along with significant increase in serum markers of hepatic damage like- aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), total bilirubin, in test groups. Further, chlorpyrifos resulted in a significant increase in lipid peroxidation of serum with decreased activities of antioxidant enzymes like superoxide dismutase (SOD) and catalase (CAT), suggesting that chlorpyrifos may cause damage of hepatic tissue due to oxidative stress. Thus, we conclude that chlorpyrifos impairs the homeostasis of haematological as well as hepatic tissue functions of rat presumably by inducing oxidative stress.